Pyrolytic conversion of waste edible oil into biofuel using sulphonated modified alumina - Amal A. Altalhi; Salwa M. Morsy; Maram T.H. Abou Kana; Nabel.A. Negm; Eslam A. Mohamed (Alexandria Engineering Journal, 2022)
Bioenergy generated from vegetable oils is an interesting alternative energy source to fossil fuel in terms of reducing carbon footprint and realizing a circular economy. The catalytic cracking route is a promising method due to its capability to process a variety of feedstocks and its ability to produce a wide range of fuels. Catalytic pyrolysis of waste edible oil was performed using heterogeneous acidic catalyst synthesized through sulphonation of modified alumina. The optimum ratio of the catalyst was 0.8 wt%, relative to the used oil, to produce 88% of liquid biofuel. The acidity of the catalyst was determined, and the analysis showed high activity compared to the recently documented heterogeneous acidic catalysts. The physical properties of the obtained biofuel including viscosity, density, acid value, cloud, pour, flash points, and cetane number were in accordance with ASTM values. Furthermore, these values were better than those recently reported. The most effective process limitation was the deposition of coke during the process, which was in its minimal value at the selected catalyst ratio. The process mechanism was discussed based on oil fatty acid composition. Engine test investigated the obtained biofuel properties, and engine performance of biofuel-diesel blends showed the suitability of the B30 blend.